SEMANTIC CHARACTERISTICS OF PHRASEOLOGISMS WITH A SOMATIC BASIS USED IN THE WORK "BOBURNOMA" - Mukhtorjon Amonov (Bright Mind Publishing, 2025)
This article analyzes the lexical-semantic characteristics of phraseologisms with a somatic basis used in "Boburnoma", the degree of use of these phraseologisms in the current Uzbek language, whether they have fallen out of use, or are limited in use.